The impact of Iskandar Malaysia development on urban amenities - Razak, Muhammad Rafeq (Malaysian Institute of Planners, 2016)
For major cities in Malaysia, globalized urban images are enthusiastically pursued by urban policy and explicitly depicted as a blueprint for a civilized city life. These developments have implications to physical and socio-economic developments as well as cultural aspects of cities in Malaysia. This is especially true for Iskandar Malaysia (IM), a new corridor development envisioned to be a "sustainable conurbation of international standing?. The whole initiatives targeted an enormous increase in socio-economic development indicators such as populations (222%), workforce (233%), and per-capita GDP (210%) during a 20-year period of 2005-2025. Since its establishment in 2006, Iskandar Malaysia has witnessed wide spread urban renewal and new urban/suburban projects which resulted in distinct physical and socio-economic changes. One of the challenges to urban consumption is the provision and allocation of amenities to people within the region. A main concern of this paper is to identify the impact of Iskandar Malaysia development on urban amenities distribution. The 2000 and 2010 census data will be explored using GIS to explain the spatial distribution of health, education and safety amenities. This information will be matched with the residential distribution to determine amenities' location, distribution and accessibility.